2022
DOI: 10.1209/0295-5075/ac63dc
|View full text |Cite
|
Sign up to set email alerts
|

Two-body hadronic decay of K+ in the presence of a circularly polarized laser field

Abstract: In this study, we have investigated the two-body hadronic decay of the charged kaon, $ K^{+}\rightarrow\pi^{+}+\pi^{0} $, in the presence of a laser field with circular polarization. We have derived, by analytical techniques, the laser-assisted decay width and the branching ratio of the charged kaon decay via the two-body hadronic channel. We have also taken into consideration the impressive results obtained for the laser-assisted charged kaon decay via the leptonic mode in order to understand more clearly the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…Another important point to mention here is that the order of magnitude of the differential partial decay width is also influenced by the laser field, since it decreases by increasing the electric field strength ξ 0 . This result is in full agreement with other researches which treated the decay processes [9,20].…”
Section: Numerical Results and Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Another important point to mention here is that the order of magnitude of the differential partial decay width is also influenced by the laser field, since it decreases by increasing the electric field strength ξ 0 . This result is in full agreement with other researches which treated the decay processes [9,20].…”
Section: Numerical Results and Discussionsupporting
confidence: 93%
“…From this figure, it is clear that if we increase the field strength ξ 0 the lifetime also increases, especially when it exceeds a threshold equal to 10 5 V cm −1 . These results obtained are similar to those found in the case of the Z-boson [11], pion [22] and kaon decays [8,9]. To interpret these results, we refer to the Turing paradox which was discovered in 1954 by Alan Turing.…”
Section: Numerical Results and Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Nowadays, such high-power laser systems motivate researchers to study fundamental processes in electroweak and quantum electrodynamics in the presence of a strong electromagnetic field realistic in experiments. Some typical processes in high energy are laser-assisted scattering [12][13][14][15] and decay processes [16][17][18]. In [19], we have discussed the effect of a strong electromagnetic field with a circular polarization on the cross section of the charged Higgs pair production in the Inert Higgs Doublet Model (IHDM).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, several authors have been interested in the study of particle physics interactions inside an external field. In addition, in Refs [4][5][6], the authors show that the electromagnetic field could affect the physical properties of a particle such as its decay width and lifetime. In Refs [7][8][9][10], we have studied the muon pair production and Higgs pair production inside a laser field with circular polarization, and we have indicated that the total cross-section is affected significantly by the laser field.…”
mentioning
confidence: 99%